Security and Defence: Ethical and Legal Challenges in the Face of Current Conflicts
XVIII, 243 p. 21 illus., 20 illus. in color.
Keywords: This book aspires to face the challenge of analyzing with due academic rigor, always in the paradigm of security and advanced sciences, but without forgetting the ethical questions that our world raises every day. The work is divided into two main sections: the first section is focused on the cyber world, with not only technical but also legal derivations given the expansion of vulnerabilities and our technological dependence. The second section, with a more interdisciplinary nature, runs through undeniably topical issues such as territorial problems and the potential decline of the traditional States, the communicational impact of information management and false news, or the commitment to essential freedoms for the West. This book connects advanced technologies and ethical issues and includes discussions on recent crises such as COVID-19. It also provides an interdisciplinary view on the ethical issues for security technologies.